The relationship between serum albumin and prostate-specific antigen: A analysis of the National Health and Nutrition Examination Survey, 2003–2010 - Xu, Kailiang; Yan, Youji; Cheng, Cong; Li, Shiqin; Liao, Yixiang; Zeng, Jinmin; Chen, Zhongjun; Zhou, Jiajie (Frontiers in Public Health, 2023)
Abstract Background: Previous study has reported that serum albumin has been associated with prostate cancer (PCa), but not with prostate-specific antigen(PSA) levels in populations without PCa history. Hence, we analyzed secondary data provided by the National Health and Nutrition Examination Survey (NHANES) (2003-2010). Methods: We selected 5469 participants from the NHANES (2003-2010) database in total. In this study, serum albumin and PSA level were considered as independent and dependent variables, serially. A number of covariates were included in this study, including demographic, dietary, physical examination, and comorbidity data. Using weighted multivariate linear regression model and smooth curve fitting, the linear and nonlinear relationship between serum albumin and PSA was investigated. Results: The weighted multivariate linear regression analysis showed that serum albumin did not independently predict PSA levels after modulating underlying interference factors (β=-0.009 95%CI:-0.020, 0.002). Nevertheless, a nonlinear relationship was found between serum albumin and PSA, with a point of 41g/L. Left of the inflection point, the effect size, 95%CI, and P value were 0.019 (log2 transformation) (-0.006, 0.043) and 0.1335, respectively. There was a negative association between serum albumin and PSA on the right side of the inflection point, with an effect size, 95%CI, and P value of -0.022(log2 transformation) (-0.037, -0.007), 0.0036. Conclusions: Serum albumin and PSA levels are not linearly related. When serum albumin levels exceed 41 g, serum albumin levels are negatively associated with PSA levels. Keywords: Serum albumin, Prostate-specific antigen (PSA), NHANES database; Nonlinear relationship; Inflection point